Two novel hyphomycetes associated with ferns from China - Jing-Yi Zhang; Kevin D. Hyde; Li-Juan Zhang; Song Bai; Dan-Feng Bao; Fatimah Al-Otibi; Yong-Zhong Lu (MycoKeys)
During an ongoing investigation of fungi associated with ferns in southwestern China, three hyphomycetes were discovered on the dead rachises of Angiopteris fokiensis and an unidentified fern. Based on morphology and multi-gene phylogenetic analyses, Arthrobotrys angiopteridis and Corynespora septata are introduced as new species. Arthrobotrys angiopteridis is a nematode-trapping fungus characterized by macronematous, mononematous, hyaline conidiophores, conidiogenous cells with polyblastic denticles at each node, and 0–1-septate, clavate to elongate pyriform, hyaline conidia. Corynespora septata features macronematous, mononematous, pale brown to dark brown conidiophores, integrated, monotretic conidiogenous cells and up to 7-distoseptate with one true septum, subcylindrical to obclavate, hyaline to pale brown conidia. Detailed descriptions and illustrations of these two new species are provided, along with morphological comparisons of the new taxa with closely related species.